Unpasteurised milk consumption as a potential risk factor for toxoplasmosis in females with recurrent pregnancy loss. (16th November 2020) - Rehman, Farhat; Shah, Mohsin; Ali, Asif; Ahmad, Irshad; Sarwar, Muhammad Tahir; Rapisarda, Agnese Maria Chiara; Cianci, Antonio
Abstract: In women with a bad obstetric history, certain infections are associated with recurrent foetal loss. One of the common infectious agents is a protozoan parasite, Toxoplasma gondii . The aim of this study was to assess unpasteurised milk consumption as a potential risk factor for toxoplasmosis in females with recurrent pregnancy loss from the province of Khyber Pakhtunkhwa, Pakistan. In this study, we recruited a total of 360 females, comprising a study group of 180 females with previous history of recurrent pregnancy loss and a control group of 180 females with no such history. Blood serum from the participants was analysed for Toxoplasma gondii IgM antibodies by enzyme linked immunosorbent assay. Among the study group, 23 (12.8%) females were serologically positive for IgM antibodies against Toxoplasma gondii, whilst 157 (87.2%) were IgM negative. In the control group, only two (4.8%) females were IgM positive, whilst 178 (95.2%) were IgM negative. Bad pregnancy outcome in the study group and control group was observed to be significantly different ( p  < .0001). In both of these groups, unpasteurised milk consumption was found as a major risk factor for Toxoplasma gondii infection. A routine serological investigation should be carried out in pregnant women to rule out toxoplasmosis and reduce the risk of recurrent pregnancy loss as well as congenital toxoplasmosis in newborns. Impact statement: What is already known on this subject? Seropositivity for Toxoplasma gondii antibodies ranges from 7% to 51% in different regions of the world. The prevalence rate varies because of differences in climate, culture, food habits, behaviour, personal hygiene and cooking habits of different societies and ethnic groups. Various risk factors have been identified that contribute to a high prevalence rate of the disease, including consumption of raw or poorly cooked meat, physical contact with cats or cat litter, consumption of unwashed raw vegetables and fruits, drinking of contaminated water and milk. We presumed that consuming unpasteurised milk could be a potential risk factor for developing toxoplasmosis in pregnant women. What the results of this study add? This study demonstrates high seroprevalence of T o xoplasma gondii antibodies in females of child bearing age that have consumed unpasteurised milk and is a potential risk factor for developing toxoplasmosis. What the implications are of these findings for clinical practice and/or further research? Our findings suggest that primary preventive measures (personal hygiene, frequent hand washing and consuming pasteurised milk) should be taken by health surveillance authorities to focus on families, especially pregnant women, to educate them about personal hygiene, contact with cattle or using their milk and milk products. The latter is especially important to aware them about the hazards of consuming unpasteurised and contaminated milk.